Dialectical behaviour therapy for posttraumatic stress disorder related to childhood sexual abuse: a pilot study in an outpatient treatment setting = Terapia cognitiva dialéctica para el Trastorno de Estrés Postraumático(TEPT) relacionado con abuso sexual infantil: un estudio piloto en undispositivo de tratamiento ambulatorio - Steil, Regina; Dittmann, Clara; Müller-Engelmann, Meike; Dyer, Anne; Maasch, Anne-Marie; Priebe, Kathlen (European journal of psychotraumatology, 2018)
Background: Dialectical behaviour therapy for posttraumatic stress disorder (DBT-PTSD), which is tailored to treat adults with PTSD and co-occurring emotion regulation difficulties, has already demonstrated its efficacy, acceptance and safety in an inpatient treatment setting. It combines elements of DBT with trauma-focused cognitive behavioural interventions. Objective: To investigate the feasibility, acceptance and safety of DBT-PTSD in an outpatient treatment setting by therapists who were novice to the treatment, we treated 21 female patients suffering from PTSD following childhood sexual abuse (CSA) plus difficulties in emotion regulation in an uncontrolled clinical trial. Method: The Clinician Administered PTSD Symptom Scale (CAPS), the Davidson Trauma Scale (DTS), the Borderline Section of the International Personality Disorder Examination (IPDE) and the Borderline Symptom List (BSL-23) were used as primary outcomes. For secondary outcomes, depression and dissociation were assessed. Assessments were administered at pretreatment, post-treatment and six-week follow-up. Results: Improvement was significant for PTSD as well as for borderline personality symptomatology, with large pretreatment to follow-up effect sizes for completers based on the CAPS (Cohens d = 1.30), DTS (d = 1.50), IPDE (d = 1.60) and BSL-23 (d = 1.20). Conclusion: The outcome suggests that outpatient DBT-PTSD can safely be used to reduce PTSD symptoms and comorbid psychopathology in adults who have experienced CSA. (PsycINFO Database Record (c) 2018 APA, all rights reserved)